"STRANGE ITEMS" IN UZBEK FOLKLORE AND THEIR MYTHOPOETIC INTERPRETATION - Rasulova Zebiniso (Journals Park Publishing, 2022)
Most of these items, which serve as a means of protection, were widely used in various magical rituals and worship rituals of primitive people. The information about them is illustrated and artistically polished in magical tales. Consequently, "strange things" are so embedded in the artistic structure of the fairy tale that if the name of any "strange thing" in the traditional text, which has been polished for centuries in the repertoire of clever storytellers, is changed, the artistic nature of the work will be damaged. Therefore, the study of the artistic role and tasks of "strange things" in the poetic construction of fairy tales is one of the general theoretical issues of folklore studies. The article mentions the mythopoetic features of strange objects in Uzbek folklore.
Keywords: fairy tales, magical objects, strange objects, folklore, mythopoetic interpretation.